ANALISIS DAMPAK KEBIJAKAN PENGEMBANGAN PARIWISATA BUDAYA TERHADAP KESEJAHTERAAN MASYARAKAT ADAT OSING DI KABUPATEN BANYUWANGI - Purnomo, Hari; Dewi, Made Heny Urmila (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
The purpose of this study is to analyze the impact of cultural tourism development policies on the participation of the Osing community, analyze the impact of cultural tourism development policies and community participation on the welfare of the Osing people and to analyze community participation in mediating the impact of cultural tourism development policies on the welfare of the Osing people. This research was conducted in the Osing Kemiren Traditional Village, Glagah District, Banyuwangi Regency. The sampling technique used in this research is the census method. The data analysis technique used is SEM analysis technique with alternative PLS. The results of this study indicate that the impact of cultural tourism development policies in the Osing Kemiren Traditional Village has a positive and significant impact on community participation. The impact of the cultural tourism development policy in the Osing Kemiren Traditional Village has a positive and significant impact on the welfare of the communit and the welfare of the community. The indirect impact of the policy of developing cultural tourism in the Osing Kemiren Traditional Village on the welfare of the people in the Kemiren Village through the participation of the Osing Kemiren Indigenous community is positive and significant.